2005
DOI: 10.1099/mic.0.27646-0
|View full text |Cite
|
Sign up to set email alerts
|

Sau42I, a BcgI-like restriction–modification system encoded by the Staphylococcus aureus quadruple-converting phage π42

Abstract: The serotype F phage w42 of Staphylococcus aureus is a triple-converting bacteriophage that encodes the staphylokinase gene (sak) and the enterotoxin A gene (entA). Lysogeny results in loss of expression of the chromosomal b-haemolysin gene (hlb) (negative conversion), the expression of staphylokinase and enterotoxin A (positive conversion), and the acquisition of resistance to lysis by all 23 phages of the International Basic Set (IBS) of S. aureus typing phages. Until this study, the basis of w42 resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Prophage sequences encoding a putative RM system were identified in StauST398-5pro. Thus, the emerging CC398 isolates, all of which harbor StauST398-5pro, have a prophage-encoded RM system conferring strong protection against horizontal genetic transfer, similar to that described for the /42 prophage (Dempsey et al, 2005). This protection may confer a selective advantage over competing organisms in their environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophage sequences encoding a putative RM system were identified in StauST398-5pro. Thus, the emerging CC398 isolates, all of which harbor StauST398-5pro, have a prophage-encoded RM system conferring strong protection against horizontal genetic transfer, similar to that described for the /42 prophage (Dempsey et al, 2005). This protection may confer a selective advantage over competing organisms in their environment.…”
Section: Discussionmentioning
confidence: 99%
“…File Table 1). Lysogenization of the prophage-free isolate S124 with S100-/ lysate, containing the recombinant phage StauST398-1, resulted in resistance to a broad range of phages, similar to isolates lysogenized with the /42 prophage that encodes a powerful restriction modification (RM) system (Dempsey et al, 2005).…”
Section: Phage Resistancementioning
confidence: 99%
“…As a consequence, S. aureus lineages carry a unique combination of core variable genes, suggesting only a vertical transmission of these genes (24). Additional R-M systems were described for S. aureus, some of which were shown to be phage encoded, which may also contribute to phage exclusion (7). In addition to the host restriction, the lysogenic immunity of a resident prophage may play a role in prevalence differences.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that lysogenic bacteria are resistant to infection with homologous bacteriophages. In addition, a recent study by Dempsey et al (7) showed that 42 introduces a restriction modification system into its lysogen, making the bacterium resistant to all international basic S. aureus typing phages. Using these properties we studied whether the IEC variants were carried by related or different ␤C-s.…”
Section: Diversity Of Bacterial Strains Containing Iec Types a To Gmentioning
confidence: 99%